Towards the understanding of heavy quarks hadronization: from leptonic to heavy-ion collisions - J. Altmann; A. Dubla; V. Greco; A. Rossi; P. Skands (European Physical Journal C: Particles and Fields)
Abstract The formation of hadrons is a fundamental process in nature that can be investigated at particle colliders. As several recent findings demonstrate, with $$e^{+}e^{-}$$ e + e - collisions as a “vacuum-like” reference at one extreme, and central nucleus–nucleus as a dense, extended size system characterized by flow and local equilibrium at the opposite extreme, different collision systems offer a lever arm that can be exploited to probe with a range of heavy-flavour hadron species the onset of various hadronization processes. In this review, we present an overview of the theoretical and experimental developments. The focus is on open-heavy-flavour measurements. The comparison with model predictions and connections among the results in electron–positron, proton–proton, proton–nucleus, nucleus–nucleus collisions are discussed. After reviewing the current state, we suggest some prospects and future developments.